Akhlak Mulia Perspektif Pendidikan Islam - Muslimah, Ana; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2025)
This study explores the concept of akhlak mulia (noble character) from the perspective of Islamic education, emphasizing that akhlak is not merely a set of social norms but a manifestation of faith and individual religiosity. The research is grounded in the central aim of Islamic education, which goes beyond intellectual development to include the formation of morally upright, civilized, and spiritually responsible individuals. A qualitative method with a literature review approach was employed, analyzing both classical and contemporary sources, including the thoughts of Al-Ghazali, Ibn Miskawaih, Al-Attas, and Quraish Shihab. The study identifies the philosophical and theological foundations of akhlak in Islamic education, as well as its objectives, methods, and implementation in educational institutions. The findings reveal that the cultivation of noble character requires a holistic approach encompassing cognitive, affective, and behavioral dimensions. Furthermore, the research underscores the urgency of revitalizing moral education in response to contemporary challenges, such as value degradation and the adverse effects of technological advancement. This study contributes to enriching the paradigm of Islamic education by affirming the importance of integrating knowledge and ethics, heart and intellect, and worldly and spiritual goals within the educational process.